Highly Stable, Amide‐Bridged Autoinducing Peptide Analogues that Strongly Inhibit the AgrC Quorum Sensing Receptor in Staphylococcus aureus. (8th June 2016) - Tal‐Gan, Yftah; Ivancic, Monika; Cornilescu, Gabriel; Yang, Tian; Blackwell, Helen E.
Abstract: Blocking quorum sensing (QS) pathways has attracted considerable interest as an approach to suppress virulence in bacterial pathogens. Toward this goal, we recently developed analogues of a native autoinducing peptide (AIP‐III) signal that can inhibit AgrC‐type QS receptors and attenuate virulence phenotypes in Staphylococcus aureus . Application of these compounds is limited, however, as they contain hydrolytically unstable thioester linkages and have only low aqueous solubilities. Herein, we report amide‐linked AIP analogues with greatly enhanced hydrolytic stabilities and solubilities relative to our prior analogues, whilst maintaining strong potencies as AgrC receptor inhibitors in S. aureus . These compounds represent powerful tools for the study of QS.